Biochar effects on durum wheat (Triticum durum) under ambient and elevated atmospheric CO2 - Lorenzo Brilli; Franz-Werner Badeck; Lorenzo Genesio; Silvia Baronti; Fulvia Rizza; Clara Fares; Luigi Cattivelli; Franco Miglietta; Anita Maienza; Alessandro Zaldei; Federica Camin; Rosella Motzo; et al. (Journal of Agriculture and Food Research)
Wheat has a pivotal role in food chains and human diet, and the understanding of its productive and qualitative performance under elevated CO2 (e[CO2]) is therefore a primary research target. While e[CO2] generally boosts wheat yield and biomass, major concerns remain about the impact on qualitative traits. The use of biochar as amendment, thanks to its well-known ability to improve soil fertility and crop production and quality, could be a suitable solution to cope with the negative effect of e[CO2] on qualitative traits. To test this hypothesis, we present the results of an open field experiment investigating the combined effects of biochar application and e[CO2] on quantitative and qualitative performance of two commercial durum wheat (Triticum durum) cultivars (Aureo and Claudio). The experimental design included plots treated without [B0] or with 30 t ha−1 of biochar as amendment [B30] and grown at ambient a[CO2] and e[CO2] (570 ppm). Results indicated that biochar increased soil temperatures by +1 °C during winter, thus favouring an earlier phenology and average biomass (+10 % and +7.2 %) and yield (+13.2 % and +8.5 %) increase in both a[CO2] and e[CO2] treatments compared to the no biochar [B0] treatments. Biochar treatments also increased flag leaf chlorophyll and decreased flavonoids, and enhanced intrinsic water use efficiency due to increases in photosynthesis and decreases in stomatal conductance. Spike density, falling number and thousand kernel weight were positively and significantly altered by biochar amendment, whilst the remaining parameters mostly differed between cultivars only. By contrast, biochar application did not alleviate nitrogen reduction in grains and straw in both cultivars neither increase grain protein content, although it remained sufficient for pasta making under all treatment combinations. Accordingly, biochar use could be preferentially adopted for increasing the productivity of high-quality cultivars whose destination and industrial processing would not suffer from a decrease in quality parameters.